Predicting crowdfunding survival - analysis of the 500 most successful reward-based crowdfunding campaigns - Veltrup, Lucas Maximilian (2022)
Crowdfunding offers an alternative form of entrepreneurial finance for entrepreneurs to access capital and build a sustainable operating business with innovative ideas. Drawing on a dataset of the 500 most successful Kickstarter campaigns with combined funding of over $366mio, this paper elaborates on the core predictors for crowdfunding survival. The results show that projects with prototypes of products and first sales significantly impact survival. Similarly, a team size of at least two people promises significantly higher chances of crowdfunding project survival. Finally, contrary to findings in the existing literature on crowdfunding success, funding goals and visual signals do not significantly impact crowdfunding survival. The findings explain the success factors for successfully building a business from a crowdfunding campaign and shed light on an under-researched field of crowdfunding literature.